Development of Bis-GMA-free biopolymer to avoid estrogenicity. Issue 1 (January 2020) - Jun, Soo-Kyung; Cha, Jae-Ryung; Knowles, Jonathan C.; Kim, Hae-Won; Lee, Jung-Hwan; Lee, Hae-Hyoung
Graphical abstract: Highlights: Isosorbide-derived biopolymer (ISDB) was synthesized as a replacement of Bis-GMA based dental materials. ISDB-based biomaterial revealed comparable mechanical properties and better biocompatibility with Bis-GMA-counterpart. The release of bisphenol A under enzymatic incubation were not detected in ISDB-based materials. ISDB-based materials showed the potential usefulness as a newly developed safe biopolymer. Abstract: Objective: Although bisphenol A-glycidyl methacrylate (Bis-GMA)-based dental materials are widely used in dentistry, Estrogenicity from released bisphenol A remains a concern due to possibility of adversely affecting the growth of children and homeostasis of adults. Here, a new family of isosorbide-derived biomonomers were synthesized and experimentally utilized as a matrix of dental sealants to provide physico-mechanical and biological properties comparable to those of a conventional Bis-GMA-based material but without the the potential estrogenicity. Methods: After synthesis of isosorbide-derived biomonomers (ISDB) by light polymerization, an experimental dental sealant with different silica filler concentrations (0–15 wt%) was characterized and compared to a commercially available Bis-GMA-based sealant. Cytotoxicity and estrogenicity assays were conducted with human oral keratinocytes and estrogen-sensitive MCF-7 cells, respectively. Results: ISDB-based dental sealants exhibited typical initially smooth surfaces with depth of cure, Vickers hardness, compressive strength/modulus, water resorption/solubility, and flowability comparable to those of the commercial sealant and met the ISO standard for dental sealants and polymer-based restorative materials. Indirect cytotoxicity tests using an extract showed comparable viability among experimental ISDB-based materials and a commercial Bis-GMA-incorporated control. DNA synthesis in MCF-7 cells (a marker of estrogenicity) and the release of bisphenol A under enzymatic incubation were not detected in ISDB-based materials. Significance: In conclusion, the comparable physico-mechanical properties of ISDB-based materials with their cytocompatibility and lack of estrogenicity suggest the potential usefulness of ISDBs as a newly developed and safe biomaterial.